2021
DOI: 10.1115/1.4051924
|View full text |Cite|
|
Sign up to set email alerts
|

Internal Tibial Forces and Moments During Graded Running

Abstract: The stress experienced by the tibia has contributions from the forces and moments acting on the tibia. We sought to quantify the influence of running grade on internal tibial forces and moments. Seventeen participants ran at 3.33 m/s on an instrumented treadmill at 0°, ±5°, and ±10° while motion data were captured. Ankle joint contact force was estimated from an anthropometrically-scaled musculoskeletal model using inverse dynamics-based static optimization. Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 58 publications
9
30
5
Order By: Relevance
“…Competitive runners ran with a step length that was 30% longer than recreational runners when normalized to height and 34% longer in absolute terms (CR: 1.67 (0.12) m versus RR: 1.25 (0.07) m). stance, whilst the posterior tibia was predominantly under compression, in line with earlier findings (Baggaley et al, 2021;Derrick et al, 2016;Meardon et al, 2014Meardon et al, , 2015Rice et al, 2019Rice et al, , 2023Yang et al, 2014). As hypothesized, the competitive runners experienced greater peak tibial bending moments than the recreational runners.…”
Section: Spatial-temporal Variablessupporting
confidence: 88%
See 2 more Smart Citations
“…Competitive runners ran with a step length that was 30% longer than recreational runners when normalized to height and 34% longer in absolute terms (CR: 1.67 (0.12) m versus RR: 1.25 (0.07) m). stance, whilst the posterior tibia was predominantly under compression, in line with earlier findings (Baggaley et al, 2021;Derrick et al, 2016;Meardon et al, 2014Meardon et al, , 2015Rice et al, 2019Rice et al, , 2023Yang et al, 2014). As hypothesized, the competitive runners experienced greater peak tibial bending moments than the recreational runners.…”
Section: Spatial-temporal Variablessupporting
confidence: 88%
“…The bending moments about the medial–lateral (ML) tibial centroid axis (i.e., sagittal plane) contribute to anterior and posterior tibial stresses. ML bending moments provide an indication of tibial loading and were estimated at a centroid representing the distal one‐third of the tibia in MATLAB (R2021a, MathWorks) in a customized program, using methods similar to those reported previously (Baggaley et al., 2021; Meardon et al., 2014; Rice et al., 2019). Internal forces and moments were estimated by ensuring static equilibrium at each 1% of the stance phase (Baggaley et al., 2021; Rice et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in accelerometry-based loads are also likely indicative of a ‘softer’ foot strike. There is recent evidence to suggest that ‘softer’ foot strike or running in a more flexed posture could increase muscle forces during running, causing an increase in bone loading that may be missed by accelerometry measures [ 80 ]. It has been identified that for every 1 g increase in peak positive acceleration, the likelihood of having a history of TSF increases by a factor of 1.361 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bending moments (M BE ) at the distal third of the tibia in the tibial coordinate system were estimated using a customized MATLAB program (MATLAB R2022a, Math-Works). M BE were calculated about the medial-lateral (ML) axis (i.e., sagittal plane bending contributing to anterior-posterior stress), based on earlier methods [31][32][33][34][35] and using the same calculations as previously described. 36 The resultant M BE is the sum of internal muscular forces and external reaction forces.…”
Section: Data Collection and Analysismentioning
confidence: 99%